THE EFFECT OF PALUDARIUM MEDIA OF SWAMP ECOSYSTEMS ON FIFTH GRADE STUDENTS’ SCIENCE LEARNING OUTCOMES: Pengaruh Media Paludarium Ekosistem Rawa Terhadap Hasil Belajar IPAS Kelas V Sekolah Dasar - Lita Erdiana; Budhi Rahayu Sri Wulan; Achmad ichwannudin (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
Learning science in elementary schools often encounters difficulties due to abstract material presentation and limited student engagement, especially in environmental topics such as ecosystems. Traditional teaching methods and media tend to rely heavily on verbal explanations, which may lead to low learning outcomes. This study aims to examine the influence of paludarium media—an integration of land and aquatic ecosystems in a contained environment—on the science learning outcomes of fifth grade elementary school students, specifically in the topic of swamp ecosystems. The research employed a quantitative approach using a quasi-experimental design with a pretest-posttest control group. The sample consisted of 52 fifth grade students at SDN Gelam II, divided into an experimental class using paludarium media and a control class using conventional learning methods. Data collection was conducted through written tests (pretest and posttest), and data analysis involved validity tests, reliability tests, normality tests, homogeneity tests, and independent samples t-test using SPSS. The results showed a significant difference in learning outcomes between the two groups. The experimental class experienced a higher improvement in posttest scores compared to the control group. The t-test result indicated a Sig. (2-tailed) value of 0.013, confirming that paludarium media has a statistically significant positive impact on science learning outcomes.